2014
DOI: 10.1021/bc400574z
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase-Based Chemo-Enzymatic Conjugation Approach Yields Homogeneous Antibody–Drug Conjugates

Abstract: Most chemical techniques used to produce antibody−drug conjugates (ADCs) result in a heterogeneous mixture of species with variable drug-to-antibody ratios (DAR) which will potentially display different pharmacokinetics, stability, and safety profiles. Here we investigated two strategies to obtain homogeneous ADCs based on site-specific modification of deglycosylated antibodies by microbial transglutaminase (MTGase), which forms isopeptidic bonds between Gln and Lys residues. We have previously shown that MTGa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
225
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(232 citation statements)
references
References 39 publications
4
225
0
3
Order By: Relevance
“…Site-dependent differences in pharmacokinetics, particularly in rat, were again noted. Dennler et al (2014) demonstrated an additional method involving mTG catalyzed crosslinking, but lacking the requirement for any engineering of the antibody cDNA sequence. The approach takes advantage of conserved heavy chain residue glutamine-295, which is the only site recognized by mTG in deglycosylated IgG.…”
Section: B Uniform Site-specific Conjugationmentioning
confidence: 99%
“…Site-dependent differences in pharmacokinetics, particularly in rat, were again noted. Dennler et al (2014) demonstrated an additional method involving mTG catalyzed crosslinking, but lacking the requirement for any engineering of the antibody cDNA sequence. The approach takes advantage of conserved heavy chain residue glutamine-295, which is the only site recognized by mTG in deglycosylated IgG.…”
Section: B Uniform Site-specific Conjugationmentioning
confidence: 99%
“…Schibli and co-workers reported, however, that deglycosylating IgGs at N297 exposed a glutamine residue at the 295 position to enzymatic ligation to create ADCs with a DAR of 2 (31). Further, by producing a N297 to Q297 mutant IgG1, they were able to introduce two viable sites for enzymatic labeling to create ADCs with a DAR of 4 (31,32).…”
Section: Enzymatic Ligationmentioning
confidence: 99%
“…6B). A transglutaminase derived from Streptomyces mobaraensis catalyzes transpeptidation where a primary amine-containing linker is covalently attached to the primary amide side chain of a specific glutamine (Q295) within deglycosylated antibodies, resulting in ADCs with a defined DAR of 2 (one conjugation site per heavy chain) (Jeger et al, 2010;Dennler et al, 2014). An N297Q mutation prior to this conjugation provides two more reaction sites (DAR = 4).…”
Section: Transpeptidation Using Microbial Transglutaminasementioning
confidence: 99%